Alberto Ginastera, the emergence of the CLAEM, the musical production of its first scholars, and the critical reception in Buenos Aires musical field. (Revista Argentina de Musicología, 2010)
In the early sixties the “Instituto Torcuato Di Tella” created three art centers. One of these was the “Centro Latinoamericano de Altos Estudios Musicales (CLAEM)” and its director was Alberto Ginastera. The Center granted scholarships to young Latin American composers, offered training for scholars and ordinary people, and organized several concerts in which scholars’works were included. Given the shortage of information on the musical activity of the CLAEM, I began to search for the possible reasons for such lack. This article is the synthesis of a research work that deals with Ginastera’s reputation and the reception of the CLAEM and its musical activity in Buenos Aires press from 1961 to 1966.
Keywords: CLAEM; avant-garde; representation; 20th Century Latin American music; Alberto Ginastera